(untitled) (Modern education and development, 2025)
This article analyzes the development trends of artificial intelligence technologies. It discusses the development of artificial intelligence in learning and decision-making, natural language processing, automated systems and robotics, and the impact of high-level automation and the workforce. The article analyzes the current and future trends of artificial intelligence, its opportunities and risks, as well as its role in society.